Evaluation of Jongaya Drainage System in Makassar Due to Channel Network Changes - Jasmine Rizkimukti; Yang Ratri Savitri; Anak Agung Ngurah Satria Damarnegara (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Makassar faces flooding challenges due to rapid urban development that lack of effective planning. Makassar faces heightened flood risks due to inadequate drainage infrastructure, particularly in areas with poor drainage systems and elevations between 0 and 4 meters above sea level. The city experiences substantial rainfall annually, as happened on February 13, 2023, which causes flooding at several points and is made worse by high tides. The study aims to investigate the existing conditions of the drainage channel in the Jongaya drainage system as well as evaluate the alternative condition proposed by the Public Works Agency of Makassar, assess planned flood discharge, determine channel dan Jeneberang Lama long storage capacity, and identify necessary drainage system support facilities.  Based on the simulation analysis results using Storm Water Management Model (SWMM) 5.2, flooding still occurs in the existing condition with a volume of 169,521 m³, as well as in the alternative condition with a volume of 148,477 m³. An evaluation was conducted for both conditions involving redesigning cross-sections, adjusting elevations, and planning 4 pumps and 2 sluice gates at the storage area outlet, which subsequently eliminated flooding in both conditions. The flood design observed in both conditions are 103.43 m³/s and 77.48 m³/s respectively.